Agronomical and physiological factors affecting growth, development and yield of sweet potato in Ethiopia - Hammes, Pieter Snyman, 1941- (University of Pretoria, 2013)
Thesis (PhD (Plant Production and Soil Science))--University of Pretoria, 2005.